Dynamic deformation and failure of ultrafine-grained titanium. (15th February 2017) - Li, Zezhou; Wang, Bingfeng; Zhao, Shiteng; Valiev, Ruslan Z.; Vecchio, Kenneth S.; Meyers, Marc A.
Abstract: Dynamic deformation and shear localization of ultrafine-grained (∼120 nm) pure titanium are examined. The strain hardening can be considered as having two regimes: below and above a strain ∼0.04; at this point there is a drastic decrease in the slope. The strain-rate sensitivity of ultrafine-grained titanium is found to be approximately the same as its coarse grained counterpart. Based on experimentally determined parameters, the Zerilli-Armstrong equation is modified to describe the mechanical response of the ultrafine-grained titanium over the strain rate range 10 −5 to 10 3 s −1 . Adiabatic shear banding is examined in a forced shear configuration where large strain is imposed in a narrow region. The microstructure inside the adiabatic shear band consists of a mixture of elongated grains and equiaxed nanograins (∼40 nm) that are significantly smaller than the initial grains (∼120 nm). The formation of equiaxed nanograins is modeled through a mechanism of rotational dynamic recrystallization. This further reduction in grain size from the one generated by ECAP is interpreted in terms of the Zener-Hollomon parameter for quasistatic and dynamic deformation. The adiabatic shear band eventually fractures by a combination of brittle and ductile failure. Graphical abstract: Image 1